Higher tacrolimus trough levels and time in the therapeutic range are associated with the risk of acute rejection in the first month after renal transplantation - Thi Van Anh Nguyen; Huu Duy Nguyen; Thi Lien Huong Nguyen; Viet Thang Le; Xuan Kien Nguyen; Viet Tien Tran; Dinh Tuan Le; Ba Thang Ta (BMC Nephrology, 2023)
Abstract Background Tacrolimus trough levels (C0) are used in most transplant centres for therapeutic drug monitoring (TDM) of tacrolimus (Tac). The target range of Tac C0 has been remarkably changed, with a target as low as 3–7 ng/ml in the 2009 European consensus conference and a target of 4–12 ng/ml (preferably to 7–12 ng/ml) following the second consensus report in 2019. Our aim was to investigate whether reaching early Tac therapeutic targets and maintaining time in the therapeutic range (TTR) according to the new recommendations may be necessary for preventing acute rejection (AR) during the first month after transplantation. Methods A retrospective study including 160 adult renal transplant patients (113 men and 47 women) with a median age of 36.3 (20–44) years was conducted between January 2018 and December 2019 at 103 Military Hospital (Vietnam). Tac trough levels were recorded in the first month, and episodes of AR were confirmed by kidney biopsy. Tac TTR was calculated as the percentage of time within the target range of 7–12 ng/ml, according to the 2019 second consensus report. Multivariate Cox analysis was performed to identify the correlation between the Tac target range and TTR with AR. Results In the first month after RT, 14 (8.8%) patients experienced AR. There was a significant difference in the incidence of AR between the Tac level groups of < 4, 4–7 and > 7 ng/ml (p = 0.0096). In the multivariate Cox analysis, after adjusting for related factors, a mean Tac level > 7 ng/ml was associated with an 86% decreased risk of AR compared with that of 4–7 ng/ml in the first month (HR, 0.14; 95% CI, 0.03–0.66; p = 0.0131). Every 10% increase in TTR was associated with a 28% lower risk of AR (HR, 0.72; 95% CI, 0.55–0.94; p = 0.014). Conclusion Gaining and maintaining Tac C0 according to the 2019 second consensus report might reduce the risk of AR in the first month following transplantation.